1980
DOI: 10.1099/00221287-116-1-143
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of Ammonia During Sporogenesis of Saccharomyces cerevisiae: Effect of Ammonia and Glutamine

Abstract: ~Comparison of the pools of glutamic acid and glutamine and of the specific activities of glutamine synthetase and glutamate dehydrogenases in sporulating a/cc and non-sporulating a/cc cells of Saccharomyces cerevisiae revealed a difference in their nitrogen metabolism.Glutamhe synthetase and glutamine appeared to be necessary for the sporulation process, glutamine playing, at least, a catabolic role. However, exogenous glutamine as well as ammoniainhibited sporulationwhile glutamic acid did not. Glutamine see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1983
1983
1987
1987

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…The mechanism of this effect is unknown for there is a lack of agreement on whether NH,+ itself participates directly, or whether it is due to derivatives (e.g. glutamine) synthesized from it (Piiion, 1977;Dubois et al, 19'77;DurieuTrautmann & Delavier-Klutchko, 1977 ;Delavier-Klutchko et al, 1980). Ammonium ion and glutamine are reported to have at least two sites of action: one quite early preventing RNA, protein and glycogen synthesis, and affecting pre-meiotic DNA synthesis; the ,other later when DNA synthesis is completed (Durieu-Trautmann & Delavier-Klutchko, 1977;DelavierKlutchko & Durieu-Trautmann, 1978;Delavier-Klutchko et al, 1980;Piiion, 1977;Croes et al, 1978).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of this effect is unknown for there is a lack of agreement on whether NH,+ itself participates directly, or whether it is due to derivatives (e.g. glutamine) synthesized from it (Piiion, 1977;Dubois et al, 19'77;DurieuTrautmann & Delavier-Klutchko, 1977 ;Delavier-Klutchko et al, 1980). Ammonium ion and glutamine are reported to have at least two sites of action: one quite early preventing RNA, protein and glycogen synthesis, and affecting pre-meiotic DNA synthesis; the ,other later when DNA synthesis is completed (Durieu-Trautmann & Delavier-Klutchko, 1977;DelavierKlutchko & Durieu-Trautmann, 1978;Delavier-Klutchko et al, 1980;Piiion, 1977;Croes et al, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…glutamine) synthesized from it (Piiion, 1977;Dubois et al, 19'77;DurieuTrautmann & Delavier-Klutchko, 1977 ;Delavier-Klutchko et al, 1980). Ammonium ion and glutamine are reported to have at least two sites of action: one quite early preventing RNA, protein and glycogen synthesis, and affecting pre-meiotic DNA synthesis; the ,other later when DNA synthesis is completed (Durieu-Trautmann & Delavier-Klutchko, 1977;DelavierKlutchko & Durieu-Trautmann, 1978;Delavier-Klutchko et al, 1980;Piiion, 1977;Croes et al, 1978). NH: does not inhibit the initiation of pre-meiotic DNA synthesis (Piiion, 1977), but it is reported that DNA synthesis (post initiation) is arrested by NH,+ (Piiion, 1977), or at least reduced and slowed down by NH,+ or glutamine (Durieu-Trautmann & Delavier-Klutchko, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…meiosis and ascospore formation) in Saccharomyces cerevisiae is induced by transferring diploid vegetative yeast cells from a rich medium (usually with high levels of glucose and complex nitrogen sources) to a nitrogen-free medium [9][10][11][12]. Within 2 h of the transfer, NAD-GDH activity in the yeast cells in repressed to about 5% of its level in vegetative cells, but NADP-GDH activity remains unchanged [13]. The net result is a change in the ratio of the specific activities of the two enzymes from 2.04 : 1 (NAD-GDH : NADP-GDH) to 0.10 : 1.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, therefore, the primary function of the NADP-GDH/glutamine synthetase ammonium scavenger in C. cinereus may be to remove ammonium from the environment of some process which is sensitive to ammonium inhibition. As NADP-GDH has been localized to basidia -the meiocytes -the most relevant comparison may be with meiosis and sporulation in yeast, which are inhibited by ammonium (Pinon, 1977) and dependent on glutamine synthetase activity (Delavier-Klutchko et al, 1980).…”
Section: Discussionmentioning
confidence: 99%